2009
DOI: 10.1016/j.rvsc.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of 5-HT7 receptors in smooth muscle preparations from equine duodenum, ileum, and pelvic flexure

Abstract: In horses, gastrointestinal (GI) disorders occur frequently and cause a considerable demand for efficient medication. 5-Hydroxytryptamine receptors (5-HT) have been reported to be involved in GI tract motility and thus, are potential targets for treating functional bowel disorders. Our studies extend current knowledge on the 5-HT7 receptor in equine duodenum, ileum and pelvic flexure by studying its expression throughout the intestine and its role in modulating contractility in vitro by immunofluorescence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…In contrast to the findings for 5-HT 7 receptors in horses, 34 results of the present study indicated that 5-HT 4 receptors are not colocalized with the ICC marker c-kit. The ICCs are considered important for gastrointestinal tract motility because of their role as electrical pacemakers, generating spontaneous electrical slow waves that propagate to smooth muscle cells to evoke phasic contractions.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings for 5-HT 7 receptors in horses, 34 results of the present study indicated that 5-HT 4 receptors are not colocalized with the ICC marker c-kit. The ICCs are considered important for gastrointestinal tract motility because of their role as electrical pacemakers, generating spontaneous electrical slow waves that propagate to smooth muscle cells to evoke phasic contractions.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study provides solid evidence of 5-HT 4 -IR in the MP and SMP neurons of horse intestine. Despite some functional investigations carried out on horse small and large intestine indicated the presence of 5-HT 4 in the ENS of this animal model, [23][24][25][26][27][28][29][30][31][32][33] the only immunohistochemical study carried out on horse ENS failed to detect 5-HT 4 in enteric neurons, but confirmed the presence of this serotonergic receptor on muscular layers. 31 Furthermore, a recent study by Delesalle et al 39 receptor were already observed in the rat spinal ganglia.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, 5-HT 4 seems to play a fundamental role in GI physiology and seems to be a promising pharmacological target for equine GI disorders. [23][24][25][26][27][28][29][30][31][32][33] In addition, we investigated 5-HT 4 expression in visceral extrinsic sensory nerves by analyzing spinal ganglion neurons from healthy horses and intestinal tissues from foals with lethal white foal syndrome (LWFS), i.e., ileocolonic aganglionosis, reminiscent of Hirschsprung's disease in humans. 34…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Accordingly, possible involvement of 5-HT 7 R in IBD was primarily related to the receptor expressed on smooth muscle as well as on enteric neurons and to its role in the accommodation of the circular muscle during the preparatory phase of ileal peristalsis contributing to abdominal distension and bloating during functional bowel disorders. 16 Results of our study demonstrate that 5-HT 7 R In this context, an activation of signal transduction pathways through 5-HT 7 R might play a pivotal role in progress of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…14 It has been suggested that under physiological conditions, this receptor is involved in the regulation of intestinal motility by participating in the relaxation of the colon circular muscle. 15,16 In addition, IBS is associated with the upregulated expression of 5-HT 7 R in colon suggesting an important role of this receptor in the IBS pathogenesis. 17 The 5-HT 7 R is also expressed by naive mouse T cells and upregulated after T-cell activation.…”
mentioning
confidence: 99%